Negative Effects of Framing and Adverse Selection on the Commitment Escalation in Investment Decision Making - Dina Puspita Sari; Annisaa Rahman (Enrichment : Journal of Management, 2022)
Commitment escalation is a decision making to increase or expand commitments in a particular project or investment even if the project or investment indicates failure. This research aims to obtain empirical evidence from the influences of adverse selection and negative framing on the tendency to escalate commitments. This study used a 2x2 factorial experimental design with a case instrument. Participants in this study were S2 students in the Master of Management and Master of Accounting programs as proxy managers selected with purposive sampling techniques. This study has taken 72 Financial Management and Management Accounting courses. The analytical technique used ANOVA two ways. The results indicate that adverse selection affects the tendency of commitment escalation. In addition, this study also proves the tendency for escalation of commitments influenced by negative framing